Ultra and the Campaign Against the U-Boats in World War II - Russell, Jerry C. (1980)
The problem addressed is the extent to which the United States Navy used Ultra, or Special Intelligence, in the campaign against the German U-boats. Information was gathered through published and unpublished sources. Through a chronological approach, United States Navy involvement is traced from entry into the war until its conclusion. Many factors are involved in the final outcome of the war and Ultra is only one. The Battle of the Atlantic was long and gruesome rather than short and spectacular. The United States Navy used Ultra along with technology, tactics, brilliant leadership and courageous men at sea to win the Battle of the Atlantic in World War II. The lessons for the future are clear. If the United States intends to oppose the Soviet submarine force at sea anywhere in the world, then we must maintain the lead in intelligence, tactics and technology. Further, and most importantly, we must strive to regain superiority of forces in those ocean areas where our interests are at stake.